2005
DOI: 10.2165/00002512-200522100-00003
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and Management of Male Erectile Dysfunction and Female Sexual Dysfunction in Patients with Cardiovascular Disease

Abstract: The historical basis for understanding erectile function as a neurovascular phenomenon and the advance from fanciful to effective treatment of erectile dysfunction (ED) are reviewed, with emphasis on patients with cardiovascular disease (CVD). ED occurs in 60% of CVD patients by 40 years of age. Male ED and female sexual dysfunction (FSD) diminish quality of life and often warn of occult CVD. ED is often unrecognised but is readily diagnosed during a 5-minute interview using a truncated International Index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 160 publications
1
35
0
3
Order By: Relevance
“…The link between cardiovascular disease (CVD) and sexual dysfunction in males is well-established; mild or moderate erectile dysfunction is much more common in patients with CVD (Archer et al, 2005). In contrast, sexual dysfunction in women with CVD has received limited attention (Steinke, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The link between cardiovascular disease (CVD) and sexual dysfunction in males is well-established; mild or moderate erectile dysfunction is much more common in patients with CVD (Archer et al, 2005). In contrast, sexual dysfunction in women with CVD has received limited attention (Steinke, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the mechanism of clitoral engorgement is very similar to penile erection, and thus may also be adversely affected by CVD (Steinke, 2010). Neuropathy or vascular disease resulting from CVD risk factors such as hypertension, smoking, diabetes or hyperlipidemia are known organic causes to female sexual dysfunction (Archer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 There is a strong association between sexual disorders and comorbid conditions, especially ED, CVD, and depression. [90][91][92] Depression may be an important contributing cause of ED, including decreased libido, difficulty with arousal and orgasm, and dyspareunia. 3,93,94 Changes in sexual activity after a cardiac event may impair the patient's quality of life, negatively affect psychological health, and strain marital or other important intimate relationships, which in turn may lead to depression and anxiety.…”
Section: Sexual Counseling For Same-sex Couplesmentioning
confidence: 99%
“…32 Nevertheless, some researchers believe that the complete role of this mechanism in vaginal congestion as a response to sexual arousal is still unknown. 33 In general, various plants, including ginseng, yohimbine, rose flower extract, and E angustifolia flower, have been used in traditional medicine to treat sexual dysfunction. Since Elaeagnus angustifolia flower exists in Iranian traditional medicine and no studies have been conducted in this regard, the researchers of the present study decided to use this plant for treatment of sexual dysfunction.…”
mentioning
confidence: 99%